2022
DOI: 10.1186/s12873-022-00597-6
|View full text |Cite
|
Sign up to set email alerts
|

The “unclear problem” category: an analysis of its patient and dispatch characteristics and its trend over time

Abstract: Background An effective emergency medical dispatch process is vital to provide appropriate prehospital care to patients. It increases patient safety and ensures the sustainable use of medical resources. Although Copenhagen has a sophisticated emergency medical services (EMS) system with a significant focus on public welfare, more than 10% of emergency cases are still being categorized as an "unclear problem category" (UPC) and are thus not categorized as "symptom-specific". Therefore, the objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…The Danish Index encompasses the criterion ‘unclear problem’ for patients calling with symptoms that cannot be categorised as a specific criterion such as chest pain or breathing difficulty [ 9 ]. Previous studies have reported ‘unclear problem’ to account for a considerable part of all emergency calls, ranging between 11 and 19% [ 6 , 10 , 11 ]. We recently documented that ‘unclear problem’ was the third most deadly criterion for patients calling for an ambulance, only exceeded by ‘possible cardiac arrest’ and ‘breathing difficulties’ [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Danish Index encompasses the criterion ‘unclear problem’ for patients calling with symptoms that cannot be categorised as a specific criterion such as chest pain or breathing difficulty [ 9 ]. Previous studies have reported ‘unclear problem’ to account for a considerable part of all emergency calls, ranging between 11 and 19% [ 6 , 10 , 11 ]. We recently documented that ‘unclear problem’ was the third most deadly criterion for patients calling for an ambulance, only exceeded by ‘possible cardiac arrest’ and ‘breathing difficulties’ [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent chief complaint was "chest pain", followed by "impaired consciousness" and "unclear problems", with the latter accounting for 11.6% of all patients. Previous studies have demonstrated that patients presenting with unclear or unspecific complaints are older [25]. Further, it has been shown that a significant proportion of those presenting with unspecific complaints sustained underlying severe conditions associated with increased morbidity and mortality [26].…”
Section: Discussionmentioning
confidence: 99%
“…"Unclear problems" was the largest part of the unspecified category, its characteristics has been described elsewhere. [32] The presence of non-specific complaints also underline the difficulty for healthcare professionals to perceive a life-threatening symptom/condition. On the other hand, 12.5% of all OHCA patients that called within 30 days also had a face-to-face visit with their GPs.…”
Section: Discussionmentioning
confidence: 99%